Trade Generation, Reputation, and Sell‐Side Analysts - JACKSON, ANDREW R. (Journal of Finance, 2005)
ABSTRACT This paper examines the trade‐generation and reputation‐building incentives facing sell‐side analysts. Using a unique data set I demonstrate that optimistic analysts generate more trade for their brokerage firms, as do high reputation analysts. I also find that accurate analysts generate higher reputations. The analyst therefore faces a conflict between telling the truth to build her reputation versus misleading investors via optimistic forecasts to generate short‐term increases in trading commissions. In equilibrium I show forecast optimism can exist, even when investment‐banking affiliations are removed. The conclusions may have important policy implications given recent changes in the institutional structure of the brokerage industry.